2005
DOI: 10.1590/s0031-10492005000500001
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Echimys Cuvier, 1809 (Rodentia, Echimyidae) from Brazil

Abstract: Here we describe a new species of Echimyidae Amazonian rodent, Echimys vieirai sp. nov., based on two individuals from the south bank of Amazon river between the lower Madeira river to the right bank of the Tapajós, respectively in the Brazilian states of Amazonas and Pará, Brazil. The main diagnostic characteristic of this new species is the presence of a dorsal median dark maroon stripe on the head, running from the rostrum to the nape. Skull morphology is quite similar to that of Echimys chrysurus (Zimmerma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
17

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 17 publications
0
8
0
17
Order By: Relevance
“…These aspects strongly suggest that minor and albispinus do not constitute different subspecies of a single species, but rather that they are valid biological species, able to maintain their morphological differences in close geographic proximity and in absence of barriers to dispersal (i.e., virtually in sympatry) – even if they share the same karyotype and shallow genetic divergences. According to Pessôa et al (2015b), Iack-Ximenes (2005 [an unpublished Ph.D. dissertation]) also recommends treating Trinomys minor as a species rather than as a subspecies of Trinomys albispinus . A number of potential causes could explain the yet-to-be-confirmed topology described in the species account by Pessôa et al (2015b), including incomplete lineage sorting and other more technical aspects of the analyses and/or data (e.g., saturation of sequences, biases in nucleotide composition).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These aspects strongly suggest that minor and albispinus do not constitute different subspecies of a single species, but rather that they are valid biological species, able to maintain their morphological differences in close geographic proximity and in absence of barriers to dispersal (i.e., virtually in sympatry) – even if they share the same karyotype and shallow genetic divergences. According to Pessôa et al (2015b), Iack-Ximenes (2005 [an unpublished Ph.D. dissertation]) also recommends treating Trinomys minor as a species rather than as a subspecies of Trinomys albispinus . A number of potential causes could explain the yet-to-be-confirmed topology described in the species account by Pessôa et al (2015b), including incomplete lineage sorting and other more technical aspects of the analyses and/or data (e.g., saturation of sequences, biases in nucleotide composition).…”
Section: Resultsmentioning
confidence: 99%
“…3.1 has not yet attempted to evaluate the extinction risk of Trinomys minor , and although the IUCN acknowledged that the Iack-Ximenes’s (2005) unpublished Ph.D. dissertation concluded that minor merited species-level recognition, it treated minor as a subspecies of Trinomys albispinus (see Bonvicino et al 2016). The species was not included in the official list of threatened species of Brazil (ICMBIO-MMA 2016).…”
Section: Resultsmentioning
confidence: 99%
“…These measurements and their definitions are as follow: greatest skull length (GSL), anterior-most projection of nasals to posteriormost projection of occipital region on midline of skull; nasal length (NL), greatest length of nasals at midline; rostral length (RL), diagonal distance from anterior edge of orbit lateral to lacrimal to anterior edge of nasals at midline; orbital length (OL), greatest length of orbits; rostral breadth (RB), breadth of rostrum at the suture between premaxilla and maxilla; interorbital constriction (IOC), least distance between bony orbits; mastoid breadth (MB), distance across cranium at mastoid processes; zygomatic breadth (ZB), maximum width across outside margins of zygomatic arches; condyloincisive length (CIL), anterior edge of upper incisors to posterior-most projection of occipital condyle; basilar length (BaL), posterior margins of upper incisors to anterior edge of foramen magnum; diastema length (D), posterior alveolar margin of upper incisors to anterior alveolar edge of PM4; maxillary toothrow length (MTRL), anterior alveolar edge of PM4 to posterior alveolar edge of M3; palatal length a (PLa), midline distance between posterior margins of upper incisors to anterior margin of mesopterygoid fossa; palatal length b (PLb), anterior edge of PM4 to anterior edge of mesopterygoid fossa; incisive foramina length (IFL), length of opening of foramina; bullar length (BuL), maximal distance from anterior to posterior edges of tympanic bulla; postpalatal length (PPL), posterior margin of inner aspect of zygomatic arch to a line perpendicular and tangent to greatest projection of occipital region; mesopterygoid fossa width (MPF), maximum width taken at the suture between palatine and pterygoid bones; first molar breath (M1B), greatest distance from lingual to buccal borders of crown; maxillary breadth (MaxB), greatest breadth of maxilla on outside of M3; occipital condyle width (OccW), width across outside margins of the occipital condyles; rostral depth (RD), depth of rostrum at the suture between premaxilla and maxilla; mandible length (MBL), from the lingual border of the incisors' alveoli to the posteriormost border of the postcondyloid process; mandible height (MH), shortest distance taken vertically from the uppermost part of the condyloid process to a plane passing from the lower edge of the symphiseal suture to the lowermost edge of the angular process; cranial depth (CD), vertical distance from ventral margin of bulla to top of cranium; cranial depth at M1 (CDM1). The measurements of the holotype were taken from Thomas (1928) and Iack-Ximenes et al (2005). In addition, we compared our specimens with photographs from…”
Section: Methodsmentioning
confidence: 99%
“…al 2015). Three species are currently recognized: E. chrysurus (Zimmerman, 1708), E. vieirai Iack-Ximenes, de Vivo & Percequillo, 2005, and E. saturnus Thomas, 1928. All of them allopatric; the first two are restricted to the eastern Amazonian and Guianan regions, while the third occurs in western Amazonia (Emmons et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Lara & Patton (2000) studied the evolutionary relationships of Trinomys species and proposed taxonomic changes based on a molecular phylogeny, and Iack-Ximenes (2005) examined type specimens, analysed morphological variation, and suggested taxonomic adjustments. Here we followed Pessôa et al (2015), who considered both Lara & Patton (2000) and Iack-Ximenes (2005) The absence of Trinomys in areas above 1300 metres (Bonvicino et al 1997, Geise et al 2004Attias et al 2009) indicates a low tolerance to the lower temperatures that occur in these areas. Another observation that supports this idea is the low abundance of Trinomys in the subtropical areas of southern Brazil; the southernmost occurrence of this genus was recorded at a latitude of 25° south in the state of Paraná (Cerboncini et al 2014).…”
Section: Introductionmentioning
confidence: 99%